Pentingnya Perilaku Organisasi dan Strategi Pemasaran dalam Menghadapi Persaingan Bisnis di Era Digital: Studi Kasus Usaha “SAPIRING” Sale Pisang Kering - Sischa Ayu Anggraeni; Fiernaningsih , Nilawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Every company needs organizational behavior, where organizational behavior is needed if you want to establish good communication between individuals and groups and be able understand individual behavior in an organization. In the digital era like today, where the level business high. Every company must pay attention to one very important and vital aspect in company management, namely in the filed of marketing. By using marketing concepts and strategies in running a business, targeted or effective marketing management will be more optimal. So, it can be hoped that the company can maximize the achievement of profit and non-profit, to the maximum and can face existing competition and at the same time achieve success in its business for the company concerned.